A Brief Analysis of the Application of Computer Aided Translation Tools in English Translation. Issue 3 (October 2020) - Liu, Qi
Abstract: With the deepening of reform and opening up, our country has increasingly frequent contacts with other countries. Therefore, the importance of translation work has become increasingly prominent. Relying on the continuous advancement of computer technology, computer-assisted translation has become a new development path in the translation industry. However, although computer-aided translation can greatly improve translation efficiency, there are still many problems to be solved. This article mainly analyzes some common problems in computer-assisted translation and gives relevant suggestions.